Tranexamic Acid in the Management of Upper Gastrointestinal Bleeding: an Evidence-based Case Report - Nur Atikah; Gurmeet Singh; Hasan Maulahela; Rahmat Cahyanur (Acta Medica Indonesiana)
Aim: to review the effectiveness of tranexamic acid therapy which has been proposed to reduce bleeding and in turn lower mortality rate. Methods: following literature searching based on our clinical question on Cochrane Library, PubMed, Clinical Key, EBSCO, Science Direct and Proquest, one systematic review that includes seven randomized controlled trials is obtained. The article meets validity and relevance criteria. Results: the systematic review found that there is no any clear evidence between intervention and control groups in term of mortality. Conclusion: the use of tranexamic acid to reduce mortality in patients with upper gastrointestinal bleeding is not recommended.